Pain Intensity and Function Improvement in Shoulder Impingement Syndrome with Kinesio Taping without Specific Technique - Andhitya Dwi Ananda; Tirza Z. Tamin; I Nyoman Murdana (Indonesian Journal of Physical Medicine & Rehabilitation, 2017)
Background: Shoulder Impingement Syndrome (SIS) can occur in three age groups according to the stage ofits disease. The First stage of SIS mostly occurs in below 25 years old, while the second stage occurs in 25-40years old and third stage occur above 40 years old. The effectiveness of Kinesio Taping in SIS using Kaze’stechnique or modification of the technique has been proven to have positive benefits according to the previousstudies. However, the Kinesio taping have some challenges, like it has to replaced after some days application,it cannot apply by the patient, and it has some contraindications like an infection in the affected area, deep veinthrombosis, allergy to the tape, wound, and some other conditionsMethods: This study used pre and post-trial without control on subjects with SIS. The “sham” Kinesio Tapingapplication consists of three I-strips that applied with no tension for one week, with reapplication in three days.The outcomes were Pain intensity that was measured by Visual Analog Scale (VAS), flexion, abduction, andscaption range of motion, and quality of life that scored by the Quick Disability of Arm, Shoulder, and Hand(DASH) measurement tool.Result: Study subjects were 16 people with mean age is 59-year-old. There was a significant improvement in painintensity, both with movement and nocturnal pain (p<0.05). The range of motion also showed significant improvementin all three measurements: pain-free shoulder abduction, flexion, and scaption compared to the pre-test values(p<0.05).Quick DASH score also showed significant improvement compared to the pre-test values (p<0.05).Conclusion: Kinesio Taping may represent a useful adjunct therapy in the management of SIS. Results of thepresent study may challenge the suggested mechanisms for the effectiveness of Kinesio Taping.Keywords: Kinesio taping, Kaze technique, Shoulder impingement syndrome(SIS), allergy, deep vein thrombosis,Visual Analog Scale (VAS), Quick Disability of Arm, Shoulder, and Hand (DASH)